Animal models of interstitial cystitis/bladder pain syndrome - Tay, Cindy; Grundy, Luke (Frontiers in Physiology, 2023)
Interstitial Cystitis/Bladder Pain Syndrome (IC/BPS) is a chronic disorder characterized by pelvic and/or bladder pain, along with lower urinary tract symptoms that have a significant impact on an individual's quality of life. The diverse range of symptoms and underlying causes in IC/BPS patients pose a significant challenge for effective disease management and the development of new and effective treatments. To facilitate the development of innovative therapies for IC/BPS, numerous preclinical animal models have been developed, each focusing on distinct pathophysiological components such as localized urothelial permeability or inflammation, psychological stress, autoimmunity, and central sensitization. However, since the precise etiopathophysiology of IC/BPS remains undefined, these animal models have primarily aimed to replicate the key clinical symptoms of bladder hypersensitivity and pain to enhance the translatability of potential therapeutics. Several animal models have now been characterized to mimic the major symptoms of IC/BPS, and significant progress has been made in refining these models to induce chronic symptomatology that more closely resembles the IC/BPS phenotype. Nevertheless, it's important to note that no single model can fully replicate all aspects of the human disease. When selecting an appropriate model for preclinical therapeutic evaluation, consideration must be given to the specific pathology believed to underlie the development of IC/BPS symptoms in a particular patient group, as well as the type and severity of the model, its duration, and the proposed intervention's mechanism of action. Therefore, it is likely that different models will continue to be necessary for preclinical drug development, depending on the unique etiology of IC/BPS being investigated.